World - Climate Services Operational Pathways : Pathways for Transforming Weather, Water, and Climate Services in Jamaica - World Bank (Washington, DC, 2022)
This report was commissioned by climate investment funds (CIF’s) E and L initiative to distill lessons from CIF’s pilot program on climate resilience (PPCR) support identifying, designing, and implementing hydrometeorological and climate services investments. It seeks to generate learning and strategic insight into the different operational pathways that can be taken by national hydrological and meteorological services to develop, deliver, and strengthen hydrometeorological and climate services. The outputs from the study comprise of one synthesis report and three country studies for Jamaica, Mozambique, and Nepal. These three countries have been selected for the study due to their different institutional frameworks, hydrometeorological systems, and socio-economic context. They provide diverse in-depth insights in hydrometeorological and climate service development, delivery, and use. In this respect, the PPCR-supported Improving Climate Data and Information Management Project (ICDIMP) was selected as a case study project for Jamaica. As of December 2021, the project is still under implementation and, based on the project experience acquired so far, this country study elucidates lessons learned on the process for modernizing hydrometeorological systems and developing climate services to users. Furthermore, it offers insight into challenges and opportunities for climate services development, delivery, and use in the Caribbean countries and small island developing states. Qualitative methods, including structured interviews and literature review, were used to identify promising pathways to transform weather, water, and climate services in the three case study countries. In Jamaica, the analysis of the data collected revealed seven themes regarding critical pathways to continue to transform weather, water, and climate services in the country. These comprise of integrating hydrometeorological data resources; hydrometeorological and climate service design and delivery; fostering hydrometeorological and climate services impact through user feedback; building appropriate human capacity; strengthening national coordination; promoting international collaboration; and institutional strengthening. The report summarizes key findings and recommendations.